Geostrategic Context of Networking of National Minority Communities in Territorial Cooperation Programmes of the EU - Márton Péti; Csilla Szalóky-Hoffmann (DETUROPE)
The participation of Hungary and Hungarian regions outside of Hungary in transnational and interregional programmes within the framework of the third objective (European Territorial Cooperation) of the European Union's Cohesion Policy 2007-2013 is an indicator suitable for analysing the international networking activity of Central European national minorities. These programme areas are very well in alignment with the settlement areas of Hungarians and thus it provides a great opportunity for cooperation in the field of regional developments. The study on the participation of Hungarian organizations in and outside of Hungary in the programming period of 2007-2013 shows; however, that Hungarian organizations outside of Hungary only partly utilize their networking potential and they worked with organisations of the mother country in only a few projects. Policies on cooperation may contribute to further utilize this networking potential.